NSCLC patients with rare EGFR Ex19del/G724S mutation showed good response to afatinib combined with chemotherapy treatment: A two-case report - Wang, Huilin; Yu, Qitao; Shi, Lina; Hou, Qinhan; Dan, Liang; Liang, Chuqiao; Hong, Xiaoyu; Zhao, Yun; Ning, Ruiling (Frontiers in Oncology, 2022)
EGFR G724S mutation in exon 18 has been shown to be resistant to both first- and third-generation epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs). However, we found a rare mutation of EGFR Ex19del/G724S in two patients with lung cancer who demonstrated a favorable response to the combination of afatinib and chemotherapy. Identified by next-generation sequencing (NGS), EGFR G724S was found from a primary and a secondary tumor biopsy, respectively. Treated with afatinib combined with chemotherapy, both patients responded well and achieved progression-free survival. Analysis of acquired mutations developed during treatment using afatinib revealed that the emergence of EGFR T790M or ALK fusion was the potential mechanism of afatinib resistance. Our study lends credence to treatment using afatinib combined with chemotherapy as a viable option for patients with Ex19del/G724S.